A Polyphasic Approach for Phenotypic and Genetic Characterization of the Fastidious Aquatic Pathogen Francisella noatunensis subsp. orientalis - Ramírez-Paredes, José G.; Thompson, Kim D.; Metselaar, Matthijs; Shahin, Khalid; Soto, Esteban; Richards, Randolph H.; Penman, David J.; Colquhoun, Duncan J.; Adams, Alexandra (Frontiers in Microbiology, 2017)
Francisella noatunensis subsp. orientalis (Fno) is the causative agent of piscine francisellosis, an emerging infectious disease in Asia and Latin America. In this study two outbreaks of francisellosis were diagnosed in the UK on the basis of histopathology, electron microscopy, PCR, bacterial isolation and fulfilment of Koch’s postulates. Furthermore, a phenotypic fingerprint based on biochemical analyses, metabolic activity, chemotaxonomic composition and antimicrobial assays was generated for the novel isolates, the Fno type strain Ehime-1 from Asia and other Fno from Latin America. The genetic relatedness between the novel Fno and other Francisellaceae species was investigated by sequencing and comparing 8 housekeeping genes and the 16S rRNA-ITS-23S rRNA sequence. The phenotypic profiling indicated a high degree of similarity between the Fno taxon as all were able to metabolise dextrin, N-acetyl-D glucosamine, D-fructose, α-D-glucose, D-mannose, methyl pyruvate, acetic acid, α-keto butyric acid, L-alaninamide, L-alanine, L-alanylglycine, L-asparagine, L-glutamic acid, L-proline, L-serine, L-threonine, inosine, uridine, glycerol, D L-α-glycerol phosphate, glucose-1-phosphate and glucose-6-phosphate. The chemotaxonomic analyses indicated that 24:1 (20.3%), 18:1n-9 (16.9%), 24:0 (13.1%) 14:0 (10.9%), 22:0 (7.8%), 16:0 (7.6%) and 18:0 (5.5%) were the predominant structural fatty acids in Fno. The antimicrobial assays showed little variation between the isolates and high susceptibility to enrofloxacin, gentamicin, neomycin, streptomycin, amikacin, ciprofloxacin, gatifloxacin, nitrofurantoin, tobramycin, kanamycin, tetracycline, oxytetracycline, florfenicol, oxolinic acid and streptomycin in all the Fno analysed. In all the phylogenetic trees the Fno strains clustered together in independent branches confirming a high degree of homogeneity. Interestingly in five of the individual trees i.e mutS, putA, rpoB, the concatenated sequence and 16S rRNA-ITS-23S rRNA genes the two Francisella noatunensis ssp. diverged more from each other than from the closely related human pathogen Francisella philomiragia (Fp). The phenotypic and genetic characterisation confirmed the Fno isolates represent a solid phylo-phenetic taxon that in the current context of the genus seems to be misplaced within the species Fn. We propose the use of the present polyphasic approach in future studies to characterise strains of Fnn and Fp and verify their current taxonomic rank of Fno.